Ethiopian women’s sexual experiences and coping strategies for sexual problems after gynaecological cancer treatment: a qualitative study - Endalew G Sendo; Gashaw Yada Hundie; Teshome Habte (BMJ Open)
Objective This study explored women’s sexual experiences and coping strategies for sexual problems after gynaecological treatment.Setting The research was carried out at Tikur Anbessa Specialized Hospital, one of the two cancer centre hospitals in the country.Study design A phenomenological qualitative study design was employed in this study.Study participants Participants were recruited using purposeful sampling. Thirteen eligible study participants were interviewed face to face. Data were collected from 2 February to 15 March 2019 and analysed at the same time. For data analysis, thematic analysis was used, which comprises three stages: data reduction, data display and data conclusion.Results Four themes resulted from the analysis of individual interview data, including treatment side effects, sexual issues following radiation therapy, lack of awareness regarding cancer treatment and sexual dysfunction, and coping strategies for sexual dysfunction following gynaecological cancer treatment. Three subthemes emerged as coping mechanisms for managing sexual issues and dysfunction among Ethiopian women with gynaecological cancer: avoiding sexual intercourse, praying for healing and seeking professional help. These themes were identified as the rich and detailed account of the experiences of sexually active women who have received treatment for their cervical cancer.Conclusion This study has broadened the perspectives on sexuality in the setting of gynaecological cancer and challenged certain commonly held beliefs about sexuality after treatment. Researchers should look into how inclusive sexuality education and training may be better integrated into the training programmes of healthcare workers. More research is needed to learn how partners of women with gynaecological cancer cope with sexual changes after treatment, how the couple as a partnership negotiates changes after treatment, and the facilitators and barriers that healthcare providers face when discussing sexuality issues with patients.